2015
DOI: 10.1590/so100-720320150005209
|View full text |Cite
|
Sign up to set email alerts
|

Associação de alelos HLA e aborto espontâneo recorrente em uma população de São Luís/Maranhão, na região Nordeste do Brasil

Abstract: It was shown that the HLA-A*34 allele is a risk factor for recurrent spontaneous abortion, while the HLA-A*24 and HLA-B*35 alleles are associated with protection, and no allele of the DRB1 locus was associated with RSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…37,40 Another contribution of the immune system in spontaneous abortion is referred to as a response, in which Human Leukocyte Antigens (HLA) stimulate the maternal immune system against the presence of the fetus. 41 Regarding genetic changes, the polymorphisms of the vascular endothelial growth factor -VEGF stand out (this being an important factor in the regulation of fetal and placental angiogenesis), 8,42 VEGF 43 receptor polymorphism and growth factor polymorphism similar to insulin-2 -IGF-2 (main fetal-placental growth factor that stimulates trophoblast invasion and growth). 44 Chromosomal abnormalities represent one of the main causes of pregnancy loss, requiring a karyotype analysis in couples.…”
Section: Discussionmentioning
confidence: 99%
“…37,40 Another contribution of the immune system in spontaneous abortion is referred to as a response, in which Human Leukocyte Antigens (HLA) stimulate the maternal immune system against the presence of the fetus. 41 Regarding genetic changes, the polymorphisms of the vascular endothelial growth factor -VEGF stand out (this being an important factor in the regulation of fetal and placental angiogenesis), 8,42 VEGF 43 receptor polymorphism and growth factor polymorphism similar to insulin-2 -IGF-2 (main fetal-placental growth factor that stimulates trophoblast invasion and growth). 44 Chromosomal abnormalities represent one of the main causes of pregnancy loss, requiring a karyotype analysis in couples.…”
Section: Discussionmentioning
confidence: 99%
“…Classical HLA Class 1 (A, B, C) Currently, not many literature reports on HLA Class 1 exist. Shankarkumar et al [98] studied the HLA-A, B, and C allele subtypes of Indian URSA patients and found that HLA-A*030301, HLA-B*5701, and HLA-Cw*12021 were susceptibility genes of URSA, and HLA-A*2402, HLA-B*4006, and HLA-Cw*15021 were protective genes. The study by Silva et al [99] conducted in the Brazilian population showed that the frequency of the HLA-A*34 allele was higher in URSA patients, and the frequency of HLA-A*24 and HLA-B*35 was significantly lower in URSA patients.…”
Section: Non-classical Hla Class 1 (Hla-g and Hla-e)mentioning
confidence: 99%